A docência universitária e a importância do apoio institucional à formação pedagógica dos professores bacharéis: o caso da Unioeste/Campus Cascavel-PR - Oro , Maria Consoladora Parisotto (2012)
The main objective of this essay is to know the pedagogical conditions in the development of the teaching process at the university, for those professors that attended only the teachers´ graduation. Some authors, among them Silva and Kluber (2012); Neitzel, Ferri and Leal (2009); Pachane (2003) when refer to professors´ graduation, highlight the lack of researches that evidence the pedagogical formation of this teacher, as if this formation were something superfluous or even unnecessary. We pursue to understand the locus of the pedagogical formation of these graduated professors, through a field research directed to twelve graduation courses of UNIOESTE – Universidade Estadual do Oeste do Paraná, Campus in Cascavel. The cited study was founded in the principles of the modality of a qualitative research and with the emphasis on the comprehension technique based on the Analysis of Content (BARDIN, 1977) which tries to know the object of study as a possibility of interpreting the data through what the people say, in the dimension of the expressed data or the latent ones. Our principal hypothesis started on the possible fragility during the process of the graduation of theses professionals, and it was found that their formation sometimes didn’t even deal with didactic-pedagogical aspects considered essential in the formation or teaching performance. This way, it’s reasonable to assume the need to think over the policies of formation, to supplement such lacks. So that this situation can be over, the college or university must create its own policies that allow the continuing education of these professionals, observing that they not always find space in the programs of Stricto Sensu graduation to go through or discuss specific and fundamental issues regarding the quality of their teaching. Besides, it’s also necessary and urgent to verify the programs of post-graduation because many of their students will be teachers someday. These are some of the issues that we try to point out in our study, calling the attention of the coordinators of colleges and universities to the results of the research. It’s hoped that this way they come up with a proposal of an action that considers the didactic and pedagogical formation of the professionals that can be part of a program which can be seen as the Policy of the Institution in the Campus of Cascavel. As said by a professor of Agricultural Engineering: “It would be admirable such an action”.